Analytical Hierarchy Process (Ahp) Pada Pengambilan Keputusan Memilih Lembaga Amil Zakat - Katman, Muhammad Nasri; Patika Sari, Wiwi Marlina; Damaiyanti, Parhana; Sofyan, A. Syathir; Sudirman, Sudirman (Al-Buhuts, 2023)
This research aims to assist muzakki in making decisions when choosing a zakat amil institution using the Analytical Hierarchy Process (AHP) method. Zakat amil institutions are organizations formed by the community with the responsibility of collecting, distributing, and utilizing zakat funds. Many zakat amil institutions currently create confusion for muzakki when deciding where to fulfill their zakat obligations. In this research, the criteria used for selecting a zakat institution include Service Quality, Credibility, Transparency, Accountability, and Legal Compliance. The research results provide information in the form of rankings or priority orders of alternative choices of Zakat Amil Institutions, based on the comparison of alternative values using the Analytical Hierarchy Process. The simulation results reveal the priority order of alternatives with Laz IZI scoring 0.285 or 28.5%, Laz Dompet Dhuafa with 0.278 or 27.8%, Laz BMM with 0.244 or 24.4%, and finally, Laz Al-Azhar with 0.194 or 19.4%.